2016
DOI: 10.1038/cddis.2015.382
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and chemo-sensitizing activity of SMAC-mimetics on high-risk childhood acute lymphoblastic leukemia

Abstract: SMAC-mimetics represent a targeted therapy approach to overcome apoptosis resistance in many tumors. Here, we investigated the efficacy of the SMAC-mimetic BV6 in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). In ALL cell lines, intrinsic apoptosis sensitivity was associated with rapid cIAP degradation, NF-κB activation, TNF-α secretion and induction of an autocrine TNF-α-dependent cell death loop. This pattern of responsiveness was also observed upon ex vivo analysis of 40 primograft BCP-ALL samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
(63 reference statements)
6
18
0
Order By: Relevance
“…Attempts to improve outcomes of primary high-risk disease by intensification of existing treatment, while largely successful, carry the burden of high toxicity (43,44), thus highlighting the need for targeted therapies that could be incorporated to strengthen current combination chemotherapy regimens. Similar to a recent study using BV6 (45) combining birinapant with an induction-type regimen (VXL) significantly enhanced objective responses and prolonged leukemia regressions in two Ph-like PDXs in vivo . Importantly, no additional side effects were observed when birinapant was combined with VXL combination therapy in vivo .…”
Section: Discussionsupporting
confidence: 75%
“…Attempts to improve outcomes of primary high-risk disease by intensification of existing treatment, while largely successful, carry the burden of high toxicity (43,44), thus highlighting the need for targeted therapies that could be incorporated to strengthen current combination chemotherapy regimens. Similar to a recent study using BV6 (45) combining birinapant with an induction-type regimen (VXL) significantly enhanced objective responses and prolonged leukemia regressions in two Ph-like PDXs in vivo . Importantly, no additional side effects were observed when birinapant was combined with VXL combination therapy in vivo .…”
Section: Discussionsupporting
confidence: 75%
“…Coincubation with Etanercept significantly blocked cell death induced by SMs (Fig. d ) pointing toward a critical role of the TNF/TNFR1‐axis in SM‐induced cell death in line with previous reports . However, Etanercept is the only clinically available anti‐TNF therapy which, in addition to TNF, also blocks LTA .…”
Section: Resultssupporting
confidence: 87%
“…We identify SMs to be potent inducers of cell death in a subset of BCP‐ALL samples in line with previous reports . Interestingly, we also found that BCP‐ALL primograft samples with low or intermediate sensitivity to SM treatment are sensitized to SM‐induced killing in presence of an inhibitor of caspase activity, including Emricasan, a pan‐caspase inhibitor in clinical trials for liver cirrhosis .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations